National Register of Climacteric and Menopause - Pacheco Romero, José (2015)
In 1996, commissioned by the Peruvian Society of the Climacteric, who performed the Hormone Workshop Seminar replacement in joint activity with the Peruvian Society of Obstetrics and Gynecology and the Peruvian Society for Endocrinology, he presented the paper on the creation of a National Registry climacteric and Menopause, the reasons continue to be valid. Given the importance of the issue, I think convenient its publication in the official organ of the Peruvian Society of Obstetrics and Gynecology.